Número de ouro na educação básica: construções geométricas na sala de aula - Santos, Maria Dayane Dalysse dos (2014)
We present in this work a bit of history of a fascinating number, known, among other names, as the Golden Ratio. We also show some curiosities and mathematical properties found in this number and its relationship to the Fibonacci sequence. In addition, we present definitions and some properties of golden rectangles and triangles and of the regular pentagon and pentagram. We developed geometric constructions relating them to the Golden Ratio, and discussed how the content of geometric constructions has been losing space in the elementary and secondary curriculum over time. In order to rescue this content for the current landscape of education we suggest the use of activities that relate to the Golden Ratio, tying the geometric constructions to the Fibonacci sequence. The activities described were implemented in a public school in the city of Rio Largo / AL, with students at an elementary school. The goal was to arouse the interest of students in mathematics and in working with geometric constructions.